Step
*
1
1
of Lemma
Long-theorem
.....equality..... 
1. x : Atom
2. y : Atom
3. ¬(x = y ∈ Atom)
4. a : ℤ
5. b : ℤ
6. ∀[d:ℕ ⟶ ℕ]. ∀[k:ℕ].
     (Moessner(ℤ-rng;x;y;((a - b)*atom(x)+(b)*atom(y));d;k)
     = ([((a - b)*atom(x)+(b)*atom(y))]_d 
                                        0(y:=((k ⋅ℤ-rng 1)*atom(x)+atom(y)))*Π(i∈upto(k)).((((k - i) ⋅ℤ-rng 1)*atom(x)
                                                                                            +atom(y)))^(d (i + 1)))
     ∈ PowerSeries(ℤ-rng))
7. n : ℕ+
8. k : ℕ+
9. upto(k) ∈ bag(ℕk)
⊢ [((a - b)*atom(x)+(b)*atom(y))]_1(y:=((k ⋅ℤ-rng 1)*atom(x)+atom(y)))
= ((a + ((k - 1) * b))*atom(x)+(b)*atom(y))
∈ PowerSeries(ℤ-rng)
BY
{ TACTIC:TACTIC:(Subst' [((a - b)*atom(x)+(b)*atom(y))]_1 = ((a - b)*atom(x)+(b)*atom(y)) ∈ PowerSeries(ℤ-rng) 0
                 THEN Auto
                 ) }
1
.....equality..... 
1. x : Atom
2. y : Atom
3. ¬(x = y ∈ Atom)
4. a : ℤ
5. b : ℤ
6. ∀[d:ℕ ⟶ ℕ]. ∀[k:ℕ].
     (Moessner(ℤ-rng;x;y;((a - b)*atom(x)+(b)*atom(y));d;k)
     = ([((a - b)*atom(x)+(b)*atom(y))]_d 
                                        0(y:=((k ⋅ℤ-rng 1)*atom(x)+atom(y)))*Π(i∈upto(k)).((((k - i) ⋅ℤ-rng 1)*atom(x)
                                                                                            +atom(y)))^(d (i + 1)))
     ∈ PowerSeries(ℤ-rng))
7. n : ℕ+
8. k : ℕ+
9. upto(k) ∈ bag(ℕk)
⊢ [((a - b)*atom(x)+(b)*atom(y))]_1 = ((a - b)*atom(x)+(b)*atom(y)) ∈ PowerSeries(ℤ-rng)
2
1. x : Atom
2. y : Atom
3. ¬(x = y ∈ Atom)
4. a : ℤ
5. b : ℤ
6. ∀[d:ℕ ⟶ ℕ]. ∀[k:ℕ].
     (Moessner(ℤ-rng;x;y;((a - b)*atom(x)+(b)*atom(y));d;k)
     = ([((a - b)*atom(x)+(b)*atom(y))]_d 
                                        0(y:=((k ⋅ℤ-rng 1)*atom(x)+atom(y)))*Π(i∈upto(k)).((((k - i) ⋅ℤ-rng 1)*atom(x)
                                                                                            +atom(y)))^(d (i + 1)))
     ∈ PowerSeries(ℤ-rng))
7. n : ℕ+
8. k : ℕ+
9. upto(k) ∈ bag(ℕk)
⊢ ((a - b)*atom(x)+(b)*atom(y))(y:=((k ⋅ℤ-rng 1)*atom(x)+atom(y)))
= ((a + ((k - 1) * b))*atom(x)+(b)*atom(y))
∈ PowerSeries(ℤ-rng)
Latex:
Latex:
.....equality..... 
1.  x  :  Atom
2.  y  :  Atom
3.  \mneg{}(x  =  y)
4.  a  :  \mBbbZ{}
5.  b  :  \mBbbZ{}
6.  \mforall{}[d:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}].  \mforall{}[k:\mBbbN{}].
          (Moessner(\mBbbZ{}-rng;x;y;((a  -  b)*atom(x)+(b)*atom(y));d;k)
          =  ([((a  -  b)*atom(x)+(b)*atom(y))]\_d 
                                                                                0(y:=((k  \mcdot{}\mBbbZ{}-rng  1)*atom(x)
                                                                                            +atom(y)))*\mPi{}(i\mmember{}upto(k)).((((k  -  i)  \mcdot{}\mBbbZ{}-rng  1)*atom(x)
                                                                                                                                                +atom(y)))\^{}(d  (i  +  1))))
7.  n  :  \mBbbN{}\msupplus{}
8.  k  :  \mBbbN{}\msupplus{}
9.  upto(k)  \mmember{}  bag(\mBbbN{}k)
\mvdash{}  [((a  -  b)*atom(x)+(b)*atom(y))]\_1(y:=((k  \mcdot{}\mBbbZ{}-rng  1)*atom(x)+atom(y)))
=  ((a  +  ((k  -  1)  *  b))*atom(x)+(b)*atom(y))
By
Latex:
TACTIC:TACTIC:(Subst'  [((a  -  b)*atom(x)+(b)*atom(y))]\_1  =  ((a  -  b)*atom(x)+(b)*atom(y))  0  THEN  Auto)
Home
Index